Gems of the Gambia musical treasures from the NCAC Archives, the Gambia. Vol. 1.
"This compilation is largely the work of traditional musicians of the Gambia. The songs were culled from the NCAC oral archives which date from the 1960s to 1980s, and the archives of Radio Gambia. The griot aka gewel in Wollof, jali in Mandinka, gawlo in Fula, is a praise singer and heralder of the courts of ancient royalties and nobility in West Africa. Their trade has survived the centuries, and griots continue to be entertainers, historians, performers and repositories of genealogies."